UJI AKTIVITAS ANTIBAKTERI EKOENZIM KULIT NANAS DENGAN VARIASI WAKTU INKUBASI - Elisa Rinihapsari; Materius Kristiyanto; Nastabitha Rizindra (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
The search for environmentally friendly and sustainable sources of natural antibacterial agents has become increasingly essential in recent years. One promising alternative is the use of eco-enzymes, which are complex mixtures derived from organic waste fermentation and known to contain bioactive metabolites with antimicrobial potential. Pineapple peel, in particular, is rich in various bioactive compounds with documented antibacterial and antioxidant properties, making it a viable substrate for eco-enzyme production. This study aimed to evaluate the antibacterial efficacy of pineapple peel-derived eco-enzyme against Staphylococcus aureus and Escherichia coli, in comparison with the standard antibiotic chloramphenicol. An additional objective was to assess the influence of different incubation times on antibacterial effectiveness. An experimental design was employed using the Kirby–Bauer disk diffusion method to test the antibacterial activity of the pineapple peel eco-enzyme at concentrations of 70%, 80%, 90%, and 100%. Chloramphenicol (30 µg) served as the positive control. Statistical analysis revealed that the eco-enzyme exhibited significant antibacterial activity against both S. aureus and E. coli. Post hoc comparisons demonstrated that all eco-enzyme concentrations (100%, 90%, 80%, and 70%) were significantly different from chloramphenicol (p < 0.05). These findings indicate that the eco-enzyme effectively inhibited bacterial growth, although through a mechanism distinct from that of synthetic antibiotics. Results from the independent t-test showed no significant difference in antibacterial activity between S. aureus and E. coli (p > 0.05), suggesting that the eco-enzyme possesses broad-spectrum antibacterial properties, effective against both Gram-positive and Gram-negative bacteria. Furthermore, comparison between 18-hour and 24-hour incubation periods showed no significant difference (p > 0.05), implying that the inhibitory reaction reached its optimal level within the first 18 hours. The stable antibacterial activity observed after 18 hours indicates that the eco-enzyme maintains good functional stability against both tested bacterial strains.